1995
DOI: 10.1177/1357633x9500100106
|View full text |Cite
|
Sign up to set email alerts
|

A Telemedicine System for High-Quality Transmission of Paper Electrocardiographic Reports

Abstract: To overcome problems associated with the faxing of ECGs, we developed a telemedicine system providing fast transmission of ECGs between physicians and cardiologists at different locations. It digitized ECGs at a resolution of 300 dots/inch (118 dots/cm), processed them, and transmitted them over a standard telephone line in under one minute. The system also paged the cardiologist in order to direct him or her to the location where the ECG would be waiting for interpretation. The system enabled physicians at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In particular radiologists have used modern telecommunications systems to transmit still images of standard x rays, computed tomographs, and magnetic resonance imaging scans. Previously reported applications to cardiology have mainly involved ECG transmission 8. Most published studies have, however, only shown that particular applications are feasible and the results have not been subjected to qualitative or quantitative analysis.…”
mentioning
confidence: 99%
“…In particular radiologists have used modern telecommunications systems to transmit still images of standard x rays, computed tomographs, and magnetic resonance imaging scans. Previously reported applications to cardiology have mainly involved ECG transmission 8. Most published studies have, however, only shown that particular applications are feasible and the results have not been subjected to qualitative or quantitative analysis.…”
mentioning
confidence: 99%
“…The majority of Michigan's population and economic activity is in the Lower Peninsula. The UP region is an area of 42,600 km 2 and contains 15 rural counties, with a total population of 314,000 at a density of 7 people/km 2 , according to census data 15 . People in the UP region experience barriers to health-care that are similar to those in many rural areas throughout the United States.…”
Section: Telemedicine In the Study Regionmentioning
confidence: 99%
“…Much of the telemedicine literature to date has focused on the technology itself [1][2][3][4] and there has been little research on the organizational issues that can make or break telemedicine programmes. Even though there is evidence that managerial and administrative issues play a vital role in the effectiveness and utilization of telemedicine services, few studies have attempted to document the influence and role of structure, leadership, job roles or training [5][6][7][8] .…”
mentioning
confidence: 99%
“…Telemedicine can be used to improve the management of a patient in a remote centre where the necessary medical expertise is not available. Telemedicine has been used in numerous fields, including cardiology 1 and paediatric cardiology 2,3 . Telecardiology has been used for many years, for example for the transmission of electrocardiograms (ECGs) in order to monitor implanted pacemakers 4 .…”
mentioning
confidence: 99%